Leadership Style, Work Motivation, and Work Discipline as Predictors of Employee Performance: Evidence from Indonesia's Quick-Service Restaurant Industry - Daffa Reza Al-Habsyi; Bimo Bakazdo Arief; Febrianty Febrianty; Reza Hardian Pratama (International Journal of Business, Law, and Education, 2026)
Purpose: This study examines the effects of leadership style, work motivation, and work discipline on employee performance at Mie Gacoan, a rapidly growing Indonesian quick-service restaurant brand operated by PT Pesta Pora Abadi. The research is situated in the labor-intensive food and beverage service sector, where service speed, teamwork, and compliance with operating standards are central to organizational performance. Design/methodology/approach: The study employed an associative quantitative design using a cross-sectional questionnaire survey. Respondents were active Mie Gacoan employees selected through purposive sampling, with an inclusion criterion of at least six months of work experience. The original draft indicated a target sample of 50-100 employees; the exact number of usable responses should be inserted before final journal submission. Measures were assessed using five-point Likert-type scales and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression. Findings: The descriptive results indicate that most respondents were young employees aged 18-25 years (65%), high-school or vocational-school graduates (72%), and relatively new employees with six months to one year of tenure (54%). Work discipline had the highest mean score (M = 4.05), followed by employee performance (M = 3.95), work motivation (M = 3.92), and leadership style (M = 3.87). The regression model explained 62.1% of the variance in employee performance. Work discipline emerged as the strongest predictor (beta = 0.354), while leadership style and motivation were also reported to have positive and significant effects. Practical implications: Management should maintain fair and consistent discipline, strengthen supervisor feedback, clarify career development pathways, and provide pressure-handling training for young employees. Originality/value: The paper contributes contextual evidence on employee performance in Indonesia's quick-service restaurant sector by integrating leadership style, work motivation, and work discipline in one empirical model.